RECENT DEVELOPMENTS IN VACCINES - Abdul Haque (Journal of University Medical & Dental College, 2020)
Development of vaccines along with that of antimicrobials is the major achievement of medical science. Vaccination has eliminated a large part of the infectious diseases that once killed millions of people. A report from the World Health Organization states that today vaccines prevent 2.5 million deaths per year: Every minute five lives are saved by vaccines worldwide. It is not difficult to imagine the impact of vaccination if we just think that in the 20th century smallpox alone killed 300 million people, and that no one dies from it today because the virus has been eradicated thanks to vaccination in 1978. Furthermore, thanks to new technologies, vaccines now have the potential of preventing and treating not only communicable diseases in all ages, but also non-communicable diseases such as cancer and neurodegenerative disorders.